Kostarika: mirova dividenda za rovnosti pohlavi - Kotisova, Milus (Gender, Equal Opportunities, Research, 2006)
Our prejudices make us blind to the wealth of inspiration in the area of gender democracy making and the progress to be found outside of the Occident, in this case to that of Costa Rica. The country extasciiacutes historic milestone is undoubtedly the abolition of its army in 1948, with the ensuing cummulative effect of the so called peace dividend, particularly in education. The latter in turn played a major role in the advancement of Costa Rican women, as well as fostered in large measure a gender sensitization of the society over an arguably short span of time - much in defiance of persistent dire problems any developing country faces. The cornerstone of its nascent gender equality is the 1990 legislation: every political party must state in its statutes how it will work to ensure equality between women and men within its ranks. The electoral law stipulates a binding 40% quota for women on ballots, or else the defaulting party cannot participate in elections. Women currently account for 38,6% in the Parliament, take up almost a third of all ministerial positions, well over a third of managerial positions in the state administration and at the local level there is almost a parity balance
Keywords: Costa Rica; Gender equality; Feminist movement